2016
DOI: 10.1637/11353-122215-case
|View full text |Cite
|
Sign up to set email alerts
|

A Coronavirus Associated with Runting Stunting Syndrome in Broiler Chickens

Abstract: Runting stunting syndrome (RSS) is a disease condition that affects broilers and causes impaired growth and poor feed conversion because of enteritis characterized by pale and distended small intestines with watery contents. The etiology of the disease is multifactorial, and a large variety of viral agents have been implicated. Here we describe the detection and isolation of an infectious bronchitis virus (IBV) -like coronavirus from the intestines of a flock of 60,000 14-day-old brown/red broiler chicks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
5
10
0
1
Order By: Relevance
“…14,30,35,46 The cause of RSS is not well understood and many viruses have been described in association with this syndrome including chicken astrovirus, 10,13,14 avian nephritis virus (ANV), 7,10,34,38 chicken parvovirus, 10,15,33,48 avian reovirus, 10,34 avian rotavirus (AvRV), 31,34 and infectious bronchitis virus. 10,12 Recently, other viruses have been detected as possible agents of cystic enteritis, such as birnavirus, 19,21,27 calicivirus, 10,19,45 fowl adenovirus group-I, 8,19,24,38 and other members of the families Picornaviridae, 10,19 Siphoviridae, Myoviridae, 10 Anelloviridae, and Circoviridae as well as CRESS-DNA virus. 19 It is suggested that RSS may be caused by one or more viruses.…”
mentioning
confidence: 99%
“…14,30,35,46 The cause of RSS is not well understood and many viruses have been described in association with this syndrome including chicken astrovirus, 10,13,14 avian nephritis virus (ANV), 7,10,34,38 chicken parvovirus, 10,15,33,48 avian reovirus, 10,34 avian rotavirus (AvRV), 31,34 and infectious bronchitis virus. 10,12 Recently, other viruses have been detected as possible agents of cystic enteritis, such as birnavirus, 19,21,27 calicivirus, 10,19,45 fowl adenovirus group-I, 8,19,24,38 and other members of the families Picornaviridae, 10,19 Siphoviridae, Myoviridae, 10 Anelloviridae, and Circoviridae as well as CRESS-DNA virus. 19 It is suggested that RSS may be caused by one or more viruses.…”
mentioning
confidence: 99%
“…When CalEnt was replicated in SPF embryonated eggs, the virus was retrieved from embryo intestines, but not from allantoic fluid or the chorioallantoic membrane. After an in vivo challenge experiment with IBV CalEnt, the enteritis and stunting was successifully reproduced in a laboratory setting, suggesting an enteric tropism [14]. Despite all the efforts in characterizing the pathobiology of IBV strains with supposed enteric tropism, information on the molecular aspects of such strains are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CalEnt is an IBV variant that arose from continued virus mutations in the presence of vaccine strains. The emergence of IBV variants such as CalEnt in 2012 [14] and Cal 99 in 1999 [26,27] likely resulted from vaccine mishandling in the field, either by poor application techniques or by usage of vaccines at a lower dosage than the recommended by the manufacturer. Vaccination issues may lead to rolling reactions and back-passaging of vaccine viruses within the flock, providing opportunities for mutations and recombination events that generate novel variants over time that might circumvent vaccine immunity [28].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, coronaviruses which can cause fatal infections in humans -SARS-CoV in 2002-2003, MERS-CoV in 2012 10 and of course SARS-CoV-2 in 2019have emerged. Coronaviruses also cause large economic losses as they can cause severe diseases in farm animals such as cows 11 and chickens 12,13 as well as domestic animals such as cats. 14,15 All viruses need to bind (adhere) to host cells, as the first step in their invasion of cells and subsequent replication.…”
Section: Coronavirusesmentioning
confidence: 99%